Sistem pelacakan posisi pengguna menggunakan marker-based AR dalam menjelajahi galeri museum VR - Pius Dian Widi Anggoro (Jurnal Teknologi dan Sistem Komputer, 2019)
This study examines the user position tracking system using marker-based AR on smartphones camera. The tracking system uses a homographic algorithm integrated into the Galeri Museum VR application. In the test, the user performed exploration interactions by 6 degrees of freedom in ten different positions in the museum gallery. The physical space used in this study was 4 x 4 m2 and a marker attached to the wall in front of the user. This system results in errors in XYZ field (0.102 m, 0.047 m, 0.044 m). If the camera's orientation is not directing to the marker and the user is moving, jitter appears because of the untracked marker. The use of marker-based AR successfully applied to track the position of users who perform natural locomotion interactions in the VR environment.